URGENSI STATUS ANAK YANG LAHIR DARI PERNIKAHAN SIRI - widhy Andrian Pratama widhy; Adis Nevi Yuliani Adis Nevi; Murdiono Dion; Halimah Endang Widyaningsih Endang (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
A legitimate illegitimate child is a child born to a woman without a legal marriage bond with the man who impregnated her. From a legal perspective, the status of this child is different from a child born in a legal marriage. Although an extramarital relationship between a man and a woman can produce offspring, positive law does not consider such a relationship as a legal marriage bond. This article uses a normative research method, utilizing literature and books to analyze doctrine from a normative perspective. This approach allows researchers to gain a deeper understanding and picture of the topic being studied. The position of an illegitimate child is regulated by Article 272 of the Civil Code (KUHPer), which states that the child will be considered legitimate if recognized through a legal marriage with his father, unless born from adultery or incest. In addition, there are provisions that allow the mother to acknowledge her child before marriage or if the recognition is stated in the marriage certificate. In accordance with Article 43 Paragraph 1 of the Marriage Law, a child born outside of marriage only has a civil relationship with his mother and her family. This is in line with the decision of the Constitutional Court in Decision Number 46/PUU-VII/2010, which confirms this status in the context of Article 43 Paragraph (1) of Law Number 1 of 1974 concerning Marriage.